A formative multi-method approach to evaluating training. (October 2016) - Hayes, Holly; Scott, Victoria; Abraczinskas, Michelle; Scaccia, Jonathan; Stout, Soma; Wandersman, Abraham
Abstract: This article describes how we used a formative multi-method evaluation approach to gather real-time information about the processes of a complex, multi-day training with 24 community coalitions in the United States. The evaluation team used seven distinct, evaluation strategies to obtain evaluation data from the first Community Health Improvement Leadership Academy (CHILA) within a three-prong framework (inquiry, observation, and reflection). These methods included: comprehensive survey, rapid feedback form, learning wall, observational form, team debrief, social network analysis and critical moments reflection. The seven distinct methods allowed for both real time quality improvement during the CHILA and long term planning for the next CHILA. The methods also gave a comprehensive picture of the CHILA, which when synthesized allowed the evaluation team to assess the effectiveness of a training designed to tap into natural community strengths and accelerate health improvement. We hope that these formative evaluation methods can continue to be refined and used by others to evaluate training. Highlights: Growing challenge is to evaluate the effectiveness of trainings in a meaningful way. Seven distinct, mixed method formative evaluation strategies used for a multi-day training. Each method gave a unique picture.